2010
DOI: 10.1189/jlb.1009676
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neutrophil degranulation by S100A9 via a MAPK-dependent mechanism

Abstract: S100A9 is a proinflammatory protein, expressed abundantly in the cytosol of neutrophils and monocytes. High extracellular S100A9 concentrations have been correlated with chronic inflammatory diseases such as rheumatoid arthritis and Crohn's disease, as well as with phagocyte extravasation. This study tested the hypothesis that S100A9 induces degranulation in human neutrophils. S100A9 was found to up-regulate the surface expression of CD35 and CD66b, proteins contained in secretory vesicles and specific/gelatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 79 publications
6
72
1
1
Order By: Relevance
“…Extracellular S100A9 is known to induce the phosphorylation of MAPKs, such as p38, and JNK in human neutrophils, leading to degranulation 41 ; thus, the release of S100A9 from neutrophils and its condensed local accumulation in the central area of granulomas may result in exhaustive degranulation in an autocrine manner. Alternatively, neutrophil degranulation may be facilitated by environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular S100A9 is known to induce the phosphorylation of MAPKs, such as p38, and JNK in human neutrophils, leading to degranulation 41 ; thus, the release of S100A9 from neutrophils and its condensed local accumulation in the central area of granulomas may result in exhaustive degranulation in an autocrine manner. Alternatively, neutrophil degranulation may be facilitated by environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte alkaline phosphatase (AP) is present in both tertiary granules of mammalian neutrophils, as well as in some fish species neutrophils and heterophils [4,11]. The use of p-Nitrophenyl Phosphate as substrate for leukocyte AP has been described for mammals [26], and has been adapted in this study for use in sturegon heterophil degranulation assay.…”
Section: Introductionmentioning
confidence: 99%
“…S100A and S100A9 are known to have antimicrobial effects, transport arachidonic acid to endothelial cells and activate expression of endothelial cell adhesion molecules. Furthermore, the role of S100A8/S100A9 on degranulation (Simard et al, 2010) and on neutrophil migration (Vandal et al, 2003) has been suggested. S100A8 was recently identified as an endogenous ligand of Toll-like receptor 4 (TLR4), amplifying phagocyte activation during inflammation upstream of TNF--dependent effects.…”
Section: Pro-inflammatory Roles Of Secreted S100a8/a9: Involvement Inmentioning
confidence: 99%